Foot and ankle deformities in children with Down syndrome. (1st June 2018) - Perotti, L. R.; Abousamra, O.; del Pilar Duque Orozco, M.; Rogers, K. J.; Sees, J. P.; Miller, F.
Abstract: Purpose: Foot and ankle deformities are common orthopaedic disorders in children with Down syndrome. However, radiographic measurements of the foot and ankle have not been previously reported. The aim of this study is to describe the foot and ankle deformity in children with Down syndrome. Methods: Children who had foot and ankle radiographs in the standing weight-bearing position were selected. Three groups of patients were identified. The relationship of radiographic measurements with age, body mass index and pain is discussed. In all, 41 children (79 feet) had foot radiographs and 60 children (117 ankles) had ankle radiographs, with 15 children overlapping between Groups I and II. Results: In Group I, hallux valgus deformity was seen before ten years of age and hallux valgus angle increased afterwards. Metatarsus adductus angle showed a significant increase (p = 0.006) with obesity and was higher in patients who had foot pain (p = 0.05). In Group II, none of the ankle measurements showed a significant difference with age or body mass index percentiles. Tibiotalar angle (TTA) and medial distal tibial angle (MDTA) were higher in patients who had ankle pain. In Group III, correlation analysis was performed between the different measurements with the strongest correlations found between TTA and MDTA. Conclusion: In children with Down syndrome, radiographic evaluation of the foot and ankle reveals higher prevalence of deformities than clinical examination. However, foot and ankle radiographs are needed only for symptomatic children with pain and gait changes. Level of Evidence: Level IV - Prognostic Study